Evaluation of Safety and Medium-Term Functional Outcomes of a Medial Fixed-Bearing Unicompartmental Knee Arthroplasty with Ultra-Highly Cross-Linked Polyethylene - Richards, Megan; Dobransky, Johanna S.; Jane, Alanna A.; Dervin, Geoffrey F. (The Journal of Knee Surgery, 2020)
The primary objective of this study was to evaluate the in vivo safety of a unicompartmental knee arthroplasty design with sequentially annealed cross-linked polyethylene by evaluating reoperation rate, in particular those related to excessive polyethylene wear or breakage. The secondary objective was to examine functional outcomes via standardized questionnaires. This was a 5-year institutional review board-approved prospective single-surgeon case series of the first 152 consecutive patients with symptomatic medial unicompartmental osteoarthritis implanted with a partial knee replacement between May 2010 and December 2014. Study participants were asked to complete the Knee injury and Osteoarthritis Outcome Score (KOOS) and Western Ontario and McMaster Universities Osteoarthrtis Index (WOMAC) questionnaires at preoperation and 2 to 5 years postoperation. Major complications and all reoperations were recorded and we produced Kaplan–Meier survivorship curves with the end point of revision to TKA. Pre- and postoperative differences for KOOS and WOMAC were evaluated by paired t-tests. The median length of follow-up was 7.2 (0–9.72) years. Seven patients required revision surgery to TKA (4.9% of patients): four with progression of arthritis in other compartments, two for infection, and one for loosening of the femoral component and subsequent progression of pain. There were no failures of polyethylene. Survival of cohort was 99.3 and 97.9% at 2 and 5 years, respectively. Patients significantly improved (p-value < 0.001) between preoperative assessment and at 2 years, with no decline at 5 years postoperation. These preliminary midterm results with this fixed-bearing design and cross-linked polyethylene were encouraging with no catastrophic failures of polyethylene. Patient reported outcomes were significantly improved and revision rates were acceptable and lower than registry reported results.
Keywords: unicompartmental knee arthroplasty; highly cross-linked polyethylene; patient reported outcome measures; safety